2020
DOI: 10.1111/1462-2920.15023
|View full text |Cite
|
Sign up to set email alerts
|

Cellular life from the three domains and viruses are transcriptionally active in a hypersaline desert community

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 68 publications
0
18
0
Order By: Relevance
“…Our analysis of MAGs uncovered that these population genomes harboured a more diverse metabolic potential compared to those previously reported from desert endolithic habitats (Crits‐Christoph et al ., 2016a,b; Uritskiy et al ., 2019, 2020). For example, in addition to oxygenic photosynthesis by Cyanobacteria , several Proteobacteria , Gemmatimonidetes and Chloroflexi MAGs harboured genes involved in anoxygenic phototrophy (AP).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our analysis of MAGs uncovered that these population genomes harboured a more diverse metabolic potential compared to those previously reported from desert endolithic habitats (Crits‐Christoph et al ., 2016a,b; Uritskiy et al ., 2019, 2020). For example, in addition to oxygenic photosynthesis by Cyanobacteria , several Proteobacteria , Gemmatimonidetes and Chloroflexi MAGs harboured genes involved in anoxygenic phototrophy (AP).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, no other substrate than gypsum has been shown to harbour fungi in the hyper‐arid Atacama Desert, which might be linked to the higher water absorption capacity of this substrate (Wierzchos et al ., 2011). The higher abundance of algae at the KM site suggests that they might significantly contribute to the organic carbon budget of the community, as previously reported in halite endoliths using metatranscriptomics (Uritskiy et al ., 2020). However, even when algae were taken into account, the ratio of oxygenic phototrophs to heterotrophic taxa was lower at KM than at the more arid CL and MTQ sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NaCl-saturated brine films here are exposed to intense ultraviolet radiation and prone to cycles of salt efflorescencedeliquescence (Hallsworth, 2020). Combining metagenomic and metatranscriptomic analyses (in both light and dark conditions), Uritskiy et al (2021) identify microbes responsible for the essential metabolic functions. One important finding was that the only eukaryote of the community, a novel Dolichomastix alga, is the major contributor of photosynthetic transcripts.…”
Section: 'Ecophysiology Of Extremophiles' Special Issuementioning
confidence: 99%
“…Crits-Christoph et al ( 32 ) identified viral sequences and their potential hosts in halite endoliths of the Atacama. Additionally, Uritskiy et al ( 33 ) detected transcriptionally active viruses potentially infecting Halobacteria also inhabiting halite salt nodules in a salar located in the Atacama Desert. These niche halite host-virus relationships highlight the need to characterize the impact of viruses in broad desert soils that represent one of the largest and rapidly expanding terrestrial ecosystems on the planet (∼35% of the Earth’s land surface [ 34 ]).…”
Section: Introductionmentioning
confidence: 99%